Terms of the Political : Community, Immunity, Biopolitics - Esposito, Roberto, 1950- (Book collections on Project MUSE., 2012)
This title calls for the opening of political thought toward a re-signification of terms - such as 'community, ' 'immunity, ' 'biopolitics, ' and 'the impersonal' - in ways that affirm rather than negate life.